Comprehensive systematic review update summary: Disorders of consciousness. (4th September 2018) - Giacino, Joseph T.; Katz, Douglas I.; Schiff, Nicholas D.; Whyte, John; Ashman, Eric J.; Ashwal, Stephen; Barbano, Richard; Hammond, Flora M.; Laureys, Steven; Ling, Geoffrey S.F.; Nakase-Richardson, Risa; Seel, Ronald T.; et al.
Abstract : Objective: To update the 1995 American Academy of Neurology (AAN) practice parameter on persistent vegetative state and the 2002 case definition for the minimally conscious state (MCS) by reviewing the literature on the diagnosis, natural history, prognosis, and treatment of disorders of consciousness lasting at least 28 days. Methods: Articles were classified per the AAN evidence-based classification system. Evidence synthesis occurred through a modified Grading of Recommendations Assessment, Development and Evaluation process. Recommendations were based on evidence, related evidence, care principles, and inferences according to the AAN 2011 process manual, as amended. Results: No diagnostic assessment procedure had moderate or strong evidence for use. It is possible that a positive EMG response to command, EEG reactivity to sensory stimuli, laser-evoked potentials, and the Perturbational Complexity Index can distinguish MCS from vegetative state/unresponsive wakefulness syndrome (VS/UWS). The natural history of recovery from prolonged VS/UWS is better in traumatic than nontraumatic cases. MCS is generally associated with a better prognosis than VS (conclusions of low to moderate confidence in adult populations), and traumatic injury is generally associated with a better prognosis than nontraumatic injury (conclusions of low to moderate confidence in adult and pediatric populations). Findings concerning other prognostic features are stratified by etiology of injury (traumatic vs nontraumatic) and diagnosis (VS/UWS vs MCS) with low to moderate degrees of confidence. Therapeutic evidence is sparse. Amantadine probably hastens functional recovery in patients with MCS or VS/UWS secondary to severe traumatic brain injury over 4 weeks of treatment. Recommendations are presented separately.